Floristic characteristics and affinities in Lao PDR, with a reference to the biogeography of the Indochina peninsula. - Hua Zhu (PLoS ONE)
The flora of Laos is composed of 5,005 species in 1,373 genera and 188 families of seed plants. Floristic and geographical attributes of the flora were analyzed. Tropical floristic elements at the family and generic levels contributed a majority (62.23% of the families and 82.30% of the genera) of the flora, of which the dominant geographical elements were pantropical distribution (42.02% of families) and tropical Asian distribution (30.08% of genera). This revealed that the flora of Lao PDR is tropical in nature and has a conspicuously tropical Asian affinity. Compared with the neighbouring countries of the Indochina peninsula, the flora of Laos has similar floristic composition and geographical elements. The floras of these Indochinese countries have similarities of more than 77.84% at the generic level, which suggests that they compose an affiliated biogeographical region. However, the flora of Laos showed the highest similarity to the flora of Vietnam (92.13%), followed by Myanmar (86.01%) at the generic level, but has less East Asian and North Temperate elements than Vietnam, and less North Temperate elements than Myanmar. These differences among the compared countries could be explained by the extrusion of the Indochinese block with the uplift of the Himalayas.